2019
DOI: 10.1002/acm2.12577
|View full text |Cite
|
Sign up to set email alerts
|

Intrafraction tumor motion during deep inspiration breath hold pancreatic cancer treatment

Abstract: Purpose Beam gating with deep inspiration breath hold (DIBH) has been widely used for motion management in radiotherapy. Normally it relies on some external surrogate for estimating the internal target motion, while the exact internal motion is unknown. In this study, we used the intrafraction motion review (IMR) application to directly track an internal target and characterized the residual motion during DIBH treatment for pancreatic cancer patients through their full treatment courses. Methods and Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
49
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 21 publications
0
49
0
1
Order By: Relevance
“…Zeng et al . showed that the mean motion of an internal marker was −0.6 ± 2.3 mm in the SI direction, observed intermittently under inhalation BH conditions on kV X-ray images [ 11 ]. However, there have neither been any reports assessing the positions of pancreatic tumors on a continuous basis, nor about the relationship between internal and external marker motion during VMAT under EE–BH conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Zeng et al . showed that the mean motion of an internal marker was −0.6 ± 2.3 mm in the SI direction, observed intermittently under inhalation BH conditions on kV X-ray images [ 11 ]. However, there have neither been any reports assessing the positions of pancreatic tumors on a continuous basis, nor about the relationship between internal and external marker motion during VMAT under EE–BH conditions.…”
Section: Introductionmentioning
confidence: 99%
“…studied the reproducibility of organ movement under active breathing control in eight patients with liver cancer by repeating fluoroscopy before each treatment 24 . Very recently, we tracked the internal targets using kV images triggered during each DIBH treatment throughout the treatment course 30 …”
Section: Introductionmentioning
confidence: 99%
“…Of these techniques, BH is one of the most commonly used owing to its versatility (2). Some researchers reported that BH was clinically useful in cases with disease sites such as the lung, breast, liver, and pancreas (6)(7)(8)(9)(10)(11). At our institution, VMAT has been used clinically under BH conditions at the end-exhalation (EE) phase for pancreatic cancer (9,12).…”
mentioning
confidence: 99%
“…Several investigators have assessed positional uncertainties in pancreatic cancer under BH conditions (9)(10)(11)(12). Nakamura et al showed that the positional reproducibility of the pancreas under EE-BH conditions was 0.6 ± 3.3 mm in the superior-inferior (SI) direction, using a visual feedback technique based on daily cone-beam computed tomography (CBCT) (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation